Kajian Literatur Mobile Learning Berbasis Augmented Reality Sebagai Upaya Melatih Model Mental Siswa Dalam Pembelajaran Sains - Kartika, Aprilia Sandra; Ningrum, Rosita; Romadhan GFF, Alfiqi Gilang Nur; Febriyanti, Shinta; Giawa , Agusto Jeremia; Erika, Farah (UNIB Press, 2025)
Technology is currently developing rapidly in the education era. An Example of technology that used as learning media through a smartphone is Augmented Reality. The purpose of doing this literature review was to determine the effect of using Augmented Reality in training students' mental models of science learning. This research used narrative literature review method, by analyzing several sources of literature related with the relationship between Augmented Reality and mental models in science learning. The result of the review shows that Augmented Reality can be applied in learning science, namely chemistry, physics and biology and can train learners' mental models by combining three levels of learners by combining three levels of representation, namely macroscopic, symbolic, and submicroscopic especially in chemistry.